UPPER NILE UNIVERSITY THE EFFECT OF CONFLICT ON DEVELOPMENT IN SOUTH SUDAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Conflict is a clash of interests, values, actions, views or directions (De Bono, 1985). Conflict refers to the existence of that clash. Conflict is initiated the instant clash occurs. Generally, there are diverse interests and contrary views behind a conflict, which are revealed when people look at a problem from their viewpoint alone. Conflict is an outcome of organizational intricacies, interactions and disagreements. It can be settled by identifying and neutralizing the etiological factors. Once conflict is concluded it can provoke a positive change in the organization.When we recognize the potential for conflict, we implicitly indicate that there is already a conflict of direction, even though it may not have yet manifested itself as a clash. Confliction is the process of setting up, promoting, encouraging or designing conflict. It is a wilful process and refers to the real effort put into generating and instituting conflict. Deconfliction is the annihilation of conflict. It does not refer to negotiation or bargaining, or even to resolution of conflict: it is the effort required to eliminate the conflict.